Studying the Enteric Microbiome in Inflammatory Bowel Diseases: Getting through the Growing Pains and Moving Forward - Young, Vincent B.; Kahn, Stacy A.; Schmidt, Thomas M.; Chang, Eugene B. (Frontiers in Microbiology, 2011)
In this commentary, we will review some of the early efforts aimed at understanding the role of the enteric microbiota in the causality of IBD. By examining these studies and drawing on our own experiences bridging clinical gastroenterology and microbial ecology as part of the NIH-funded Human Microbiome Project, we hope to help define some of the “growing pains” that have hampered these initial efforts. It is our sincere hope that this discussion will help advance future efforts in this area by identifying current challenges and limitations and by suggesting strategies to overcome these obstacles.